Ten thousand islands eaudiobook - Wayne White, Randy (Doc Ford,, 2005)
Government agent-turned-marine biologist Doc Ford sails an endless sea of questions when he agrees to investigate a death from the past. Years ago, off Florida's Gulf Coast, a teenaged girl found an ancient gold medallion. Then she began having nightmares. Then she was found hanging from a tree. Now, years later, the girl's mother is being terrorized with break-ins, phone calls with no one there—and her daughter's grave has been dug up. Somebody wants that medallion. The search for answers will lead Doc through a shadowy world of ancient ritual and modern corruption, to an evil that was born in the past—but lives in the present ... "One of the most satisfying thrillers in recent memory."—Chicago Tribune